2018
DOI: 10.1111/cas.13655
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic roles of enhancer of zeste homolog 1/2 in hematological malignancies

Abstract: Polycomb group (PcG) proteins regulate the expression of target genes by modulating histone modifications and are representative epigenetic regulators that maintain the stemness of embryonic and hematopoietic stem cells. Histone methyltransferases enhancer of zeste homolog 1 and 2 (EZH1/2), which are subunits of polycomb repressive complexes (PRC), are recurrently mutated or highly expressed in many hematological malignancies. EZH2 has a dual function in tumorigenesis as an oncogene and tumor suppressor gene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 86 publications
(114 reference statements)
0
30
0
Order By: Relevance
“…33 In this study, neither abnormal clinical signs nor significant body weight loss was observed in mice throughout longterm continuous administration of OR-S1 for 150 days; therefore, long-term continuous administration would be a clinically feasible regimen. 34,51 This favorable safety profile has enabled us to move forward to clinical trials as the only clinically applicable EZH1/2 inhibitor; 29 subsequently evaluating the effect of OR-S1 against MM patients would be encouraged as a novel therapeutic option for relapsed MM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 In this study, neither abnormal clinical signs nor significant body weight loss was observed in mice throughout longterm continuous administration of OR-S1 for 150 days; therefore, long-term continuous administration would be a clinically feasible regimen. 34,51 This favorable safety profile has enabled us to move forward to clinical trials as the only clinically applicable EZH1/2 inhibitor; 29 subsequently evaluating the effect of OR-S1 against MM patients would be encouraged as a novel therapeutic option for relapsed MM.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, selective EZH2 inhibitors have been developed and some of them are currently being investigated in clinical trials against various malignant tumors, including MM. [26][27][28][29] Furthermore, upregulation of EZH2 in SP cells has been reported and this suggests that EZH2 has an important role for stem cell maintenance in MM. 10 However, it remains unclear whether EZH1, the other catalytic subunit of PRC2, is important to maintain the stemness of MM cells, although EZH1 only partially compensates for loss of EZH2 in stem cell maintenance.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, PVT1 was reported to recruit EZH2 [99] to LATS2 [100], CDKN2B and CDKN2A [101] promoters, in order to repress their transcription, suggesting a MYC-independent activity. Although this evidence was obtained in solid tumor models, the involved genes, and in particular the epigenetic regulator EZH2 are well known also in hematological malignancies [102], thus deserving further investigation.…”
Section: Pvt1 and Circpvt1: Myc Partners In Crime And Beyondmentioning
confidence: 95%
“…Because of the bimodal pathogenic functions of EZH2 as an oncogene and a tumor suppressor gene, pharmacological inhibition of EZH2 and both EZH1 and EZH2 has being tested extensively in pre-clinical and clinical studies in solid tumors, B-cell lymphoma, and AML [45]. An Ezh2 insufficiency aberrantly activates expression of certain oncogenes because of reduced levels of H3K27me3, but Ezh1-PRC2 partly compensates for Ezh2 loss in the maintenance of transcriptional repression of Ezh2 target genes [46].…”
Section: Targeting Therapy Against Ezh1 and Ezh2 In Myeloid Malignanciesmentioning
confidence: 99%